2017
DOI: 10.21475/ajcs.17.11.03.pne362
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic potential of Cymbopogon citratus over beggarticks (Bidens sp.) germination

Abstract: Allelochemicals are important and innovative tools for weed control as they neither harm the environment nor increase weed management costs. The secondary metabolites can be extracted by water or soaking and later applied in soil or leaves. This study evaluated the leaf extracts of Cymbopogon citratus, affecting germination of Bidens pilosa and B. subalternans seeds. Two trials were conducted in germination chambers. The completely randomized design was employed in both trials with 5 replications. Trial one wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
1
Order By: Relevance
“…The research revealed that the aqueous extract of C. citratus significantly reduced the seed germination rate of B. pilosa and B. subalternans . The concentrations interfered, inversely and proportionally, while reducing the germination rate [ 65 ]. A previous study was conducted on the phytotoxic potentials of aqueous leaf extracts obtained from Artemisia absinthium L. and Psidium guajava L. Evaluations were aimed at various effects on seed germination, plantlet development, enzymatic and non-enzymatic antioxidants, photosynthetic pigments, and osmolytes of Parthenium hysterophorus L. Leaf extracts of both A. absinthium and P. guajava acted to limit seed germination and plantlet development, but increased antioxidant enzyme activities [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The research revealed that the aqueous extract of C. citratus significantly reduced the seed germination rate of B. pilosa and B. subalternans . The concentrations interfered, inversely and proportionally, while reducing the germination rate [ 65 ]. A previous study was conducted on the phytotoxic potentials of aqueous leaf extracts obtained from Artemisia absinthium L. and Psidium guajava L. Evaluations were aimed at various effects on seed germination, plantlet development, enzymatic and non-enzymatic antioxidants, photosynthetic pigments, and osmolytes of Parthenium hysterophorus L. Leaf extracts of both A. absinthium and P. guajava acted to limit seed germination and plantlet development, but increased antioxidant enzyme activities [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…3). Krenchinski et al (2017) carried out a similar study on the effect of Cymbopogon citratus extract on the germination and germination speed of beggartick. Reduced plant development will consequently affect carbohydrate concentration, as they are produced by the photosynthetic process (Currey and Lopez, 2015).…”
Section: Seedling Developmentmentioning
confidence: 99%
“…Regarding competition, allelopathy is an important mechanism in which plants release chemical compounds named allelochemicals (Sharokhi et al, 2011). Allelochemicals can cause direct or indirect and positive or negative results to other plants and organisms (Krenchinski et al, 2017). By releasing the allelochemicals, plants can inhibit the germination and development of other species.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning seed germination, Hanley and Whiting (25) reported that phytotoxic allelochemicals present in the extracts appear to mediate a disruption of normal cellular metabolism, affecting reserve mobilization, a process that usually takes place during early stages of seed germination (23). The aqueous extracts of Cymbopogon citratus were allelopathic to germination of Bidens pilosa and B. subalternans (33).…”
Section: Germination and Initial Growth Assaysmentioning
confidence: 99%